2007
DOI: 10.1063/1.2710304
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic jet deposition of silver nanoparticle aerosols: Correlations of impact conditions and film morphologies

Abstract: We describe experiments and modeling for the deposition of silver lines and films via the impaction of a silver nanoparticle aerosol delivered through a supersonic jet. The aerosol gas dynamics of the jet flow field, nanoparticle acceleration in the jet, and deposition by impaction onto the substrate were modeled for both a flat-plate nozzle and for a conical nozzle designed to obtain higher impaction velocities. We modeled nanoparticle dynamics for He, Ar, and N2 gasses, all initially at room temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…The writing speed was set at 0.6 mm/s and films were written in 30 passes, resulting in a film thickness of about 25 µm. SEM observations revealed that the films are nanoparticulate with a 10-20 nm length scale and intraparticle porosity [1]. XRD Scherrer analysis confirmed that the grain size was in the range of 11.2-26.4 nm [1].…”
Section: Direct-writing Of Nanostructured Filmsmentioning
confidence: 68%
See 2 more Smart Citations
“…The writing speed was set at 0.6 mm/s and films were written in 30 passes, resulting in a film thickness of about 25 µm. SEM observations revealed that the films are nanoparticulate with a 10-20 nm length scale and intraparticle porosity [1]. XRD Scherrer analysis confirmed that the grain size was in the range of 11.2-26.4 nm [1].…”
Section: Direct-writing Of Nanostructured Filmsmentioning
confidence: 68%
“…Gas dynamics during the acceleration of the flow have been studied previously [1] and calculations show that the NPs reach a speed of approximately 1000 m/s upon impaction, which is sufficient for them to stick and form cohesive films with a relative density of ~70%. A silicon substrate was placed below the nozzle to collect the NPs, and was mounted on a computer controlled translation stage to enable the writing of films.…”
Section: Direct-writing Of Nanostructured Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LAMA process has been described in detail elsewhere [5][6][7]. In summary, a KrF excimer laser with wavelength of 248 nm, pulse width of 12-15 ns, and repetition rate of 200 Hz was focused onto a microparticle aerosol stream that was confined by a coaxial buffer gas.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoparticulate thick films can be produced by combining the LAMA process with supersonic impaction. Film densities of 60-80% have been achieved by controlling the gas type and the impaction nozzle geometry [7].…”
Section: Introductionmentioning
confidence: 99%